(untitled) (World Bulletin of Social Sciences, 2026)
This article analyzes the creation and artistic interpretation of classical poets’ image in Uzbek dramaturgy. In particular, it examines how the images of representatives of classical literature such as Alisher Novoi, Zahiriddin Muhammad Babur, and Mashrab are portrayed in Uzbek stage art and dramaturgy as well as how their lives works and spiritual heritage are reflected in dramatic works.